Introduction to the theory of cooperative games - Peleg, Bezalel. (Theory and Decision Library, Series C: Game Theory, Mathematical Programming and Operations Research, 2025)
TU Games - Coalitional TU games and solutions - The core - Bargaining sets - The Prekernel, Kernel, and Nucleolus - The Prenucleolus - Geometric properties of the ?-Core, Kernel, and Prekernel - The shapley value - Continuity properties of solutions - Dynamic bargaining procedures for the Kernel and the bargaining set - NTU Games - Cooperative games in strategic and coalitional form - The core of NTU games - The shapley NTU value and the harsanyi solution - The consistent shapley value - On the classical bargaining set and the mas-colell bargaining set for NTU games - Variants of the Davis-Maschler bargaining set for NTU games.